2017
DOI: 10.1021/acs.orglett.7b00141
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Violaceic Acid and Related Compounds through Aryl Triazene

Abstract: MPC1001 is a potent anticancer natural product that contains a violaceic acid moiety. Herein we report the total synthesis of the natural product violaceic acid and its derivative. In this approach, a triazene-directed Ullman coupling proved to be highly effective. We converted the triazene to a hydroxy group by means of a palladium-catalyzed reaction. Treatment of the triazene with trifluoroacetic acid generated an arenediazonium ion that produced an aryl radical, leading to the protodediazoniation and a tric… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…Finally, we would like to propose that it is worth investing the new triazenes in the context of radical chemistry. For some reactions of aryl triazenes, cleavage reactions of the N 3 R 2 group were suggested to give aryl radicals intermediates [5a, 53] . These suggestions are in line with the fact that aryl diazonium salts (the primary decomposition products of aryl triazenes) are known precursors for aryl radicals [54] .…”
Section: Discussionmentioning
confidence: 99%
“…Finally, we would like to propose that it is worth investing the new triazenes in the context of radical chemistry. For some reactions of aryl triazenes, cleavage reactions of the N 3 R 2 group were suggested to give aryl radicals intermediates [5a, 53] . These suggestions are in line with the fact that aryl diazonium salts (the primary decomposition products of aryl triazenes) are known precursors for aryl radicals [54] .…”
Section: Discussionmentioning
confidence: 99%
“…To achieve these aims, we selected aryl aldehydes substituted with 2-triazenyl groups (Scheme c) . The triazene group offers many potential advantages: (1) although not previously reported, the triazene group should be capable of acting as a chelating group for metal-catalyzed intermolecular hydroacylation, with the first nitrogen atom positioned to form a stable five-membered acyl-metal-hydride complex; (2) catalyst coordination to the second nitrogen atom would direct the metal center to the ortho –C–H bond; (3) the electron-donating properties of the triazene would promote electrophilic aromatic substitution reactions; (4) triazene groups can be easily removed; and (5) triazenes can be transformed to a wide range of alternative functional groups. ,, By exploiting just a selection of these activation modes, it should be possible to access multisubstituted benzenes; these are motifs that remain of considerable worth to medicinal chemists . Despite the versatility of the triazene group, its use as a directing group in metal-catalyzed C–H functionalization is rare and remains challenging .…”
mentioning
confidence: 99%
“…We next explored how readily the triazene group could be removed and replaced with a H-atom (see Scheme b). Initial attempts using either known reducing (H-SiCl 3 ) or acidic conditions (TFA) were not successful. However, we found that by using either BF 3 ·OEt 2 or triflic acid, the triazene group could be efficiently removed (Scheme b) .…”
mentioning
confidence: 99%